The Use of Manga Media to Improve Students’ Writing Skills - Abdurrazzaq, Ilham Bagas; Yulianto, Henrikus Joko; Haryanti, Rahayu Puji (English Education Journal, 2024)
Recount texts often present challenges for students due to their reliance on chronological structure, accurate use of past tense, and descriptive language, which can be difficult to master. Manga, as a visually engaging and narrative-driven medium, offers an innovative solution by simplifying complex concepts and making the learning process more interactive and enjoyable. This study explores the implementation of Manga media as a tool for teaching recount texts, emphasizing its ability to enhance students' comprehension and writing skills. A sample of thirty students from VIII A class at SMP Al Madina was selected through quota sampling for the research. A mixed-methods approach was employed to comprehensively present the results, utilizing data collected through questionnaires and tests. The result indicates that Manga media effectively enhanced students' recount text writing skills, as evidenced by improved test scores. The post-test results demonstrated a marked improvement over the pre-test, with the average score increasing from 68 in the pre-test to 74 in the post-test. The highest score improved from 76 to 82, while the lowest score increased from 60 to 65, indicating the significant impact of Manga media on student achievement. These findings suggest that Manga media is a novel tool and an effective collaborative medium for teaching recount text writing, as it fosters student engagement and improves learning outcomes.